Limites inferiores para o problema de coloração de vértices via geração de cortes e colunas - Rodrigues, Carlos Diego (2008)
In this work the vertex coloring problem is approached via integer programming. A tighter version of the independent set formulation is used, where the vertex-related constraints are substituted by subgraph-related constraints. Each constraint establishes a lower bound on the number of independent sets intersecting a subgraph H. It is shown a sufficient condition for this inequality to define a facet of the associated polytope. Basically, H is required to be color critical, not included in another color critical subgraph, and to have a connected complement. Also, the column generation algorithm proposed by Mehotra and Trick (INFORMS Journal in Computing, 1996) is adapted to allow the addition of cutting planes and to provide lower bounds along the process, which may abbreviate its end. Some computational experiments are reported.